2016
DOI: 10.2147/ndt.s108814
|View full text |Cite
|
Sign up to set email alerts
|

Association of brain-derived neurotrophic factor and nerve growth factor gene polymorphisms with susceptibility to migraine

Abstract: Migraine is one of the most common neurological diseases worldwide. Migraine pathophysiology is very complex. Genetic factors play a major role in migraine. Neurotrophic factors, such as brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), play an important role in central nervous system functioning, development, and modulation of pain. This study investigates whether polymorphisms in the BDNF and NGF genes are associated with migraine disease in a Turkish case–control population. Overall, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In addition, variants differing in allele frequencies between populations should also be considered. For example, the A allele frequencies of rs6330 between different ethnic groups were about 30–40% in Caucasian populations, and 12.8% in our Han Chinese population. Although recruiting pure Han Chinese Taiwanese participants may have minimized the effects of population stratification, further studies for other ethnic groups were warranted, to confirm our study results.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, variants differing in allele frequencies between populations should also be considered. For example, the A allele frequencies of rs6330 between different ethnic groups were about 30–40% in Caucasian populations, and 12.8% in our Han Chinese population. Although recruiting pure Han Chinese Taiwanese participants may have minimized the effects of population stratification, further studies for other ethnic groups were warranted, to confirm our study results.…”
Section: Discussionmentioning
confidence: 67%
“…The results showed that statistical significance of the allelic (Figure 3A) or the dominant (Figure 3B) model of rs6265 was lost when the study of Coskun et al (21) was excluded from the analysis (dominant OR: 1.17, 95% CI: 1.00–1.38, p  = 0.054; allelic OR: 1.14, 95% CI: 0.99–1.31, p  = 0.067). To assess the potential effects of specific study characteristics on the association between rs6265 and migraine susceptibility, we pooled the OR and 95% CI from the subgroups of migraine type and study quality.…”
Section: Resultsmentioning
confidence: 97%
“…Methodological items for quality assessment and individual item scores of each included study are illustrated in Table 2. Three studies were classified as “higher” quality studies (1921), while the remaining two studies were rated as “lower” quality studies (18, 25). Genotypic data for the BDNF gene rs6265 were available in four studies as subgroups of migraine with and without aura (18, 20, 21, 25).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that rs6330, rs2072446 and rs734194 genetic variants are associated with number of neurovascular and psychiatric diseases, which might predispose to stroke and increase its likelihood [ 23 , 24 ]. Particularly, it was shown that NGF rs6330*T minor allele is positively associated with the risk of migraine, schizophrenia and Alzheimer’s disease [ 13 , 14 , 25 ]. As for NGFR rs2072446, it was observed as being associated with depression and schizophrenia [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%